An investigation of the macroeconomic determinants of consumption spending in South Africa - Garidzirai, Rufaro; Mapanga, Arthur (Acta Universitatis Danubius. Œconomica, 2022)
Household consumption has become a force to be reckoned with in contributing to Sustainable Development Goals. Understanding the determinants that influence household consumption has become a priority especially in emerging countries. Thus, the study examined the macroeconomic factors that influence household consumption in South Africa from 1984–2021 focusing on economic growth, interest rate, unemployment, and inflation. The study is envisaged to contribute to the scant empirical literature on consumption expenditure in the South Africa’s context, thus, contributing to the macroeconomics literature body of knowledge. To achieve this aim, the study employed an Autoregressive distributive lag (ARDL) model due to its unique characteristic of forecasting and disentangling the long-run relationship among the variables from short-run relationship. The ARDL results illustrate a comprehensive outlook on the factors that contribute to consumption spending in South Africa. Amidst the most telling, in the long-run is the population growth and remittances that increases consumption spending in South Africa. Noteworthy is that unemployment, high inflation rates and high interest rates continue to create a detrimental consumption environment. Going forward a multipronged approach that includes reforming the African labour markets, creating a good political stability and employing favourable monetary policies that favours employment and lowering of interest rates should be considered